2021
DOI: 10.1109/access.2021.3064359
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Fuzzy PD Inverse Dynamics Decoupling Control of Spherical Motion Mechanism With Fuzzy Linear Extended State Observer

Abstract: In this paper, a robust adaptive fuzzy proportional-derivative inverse dynamics decoupling control scheme with fuzzy-based linear extended state observer (FLESO) is presented and applied to the trajectory tracking control of a two degree-of-freedom (2-DOF) spherical motion mechanism (SMM). The dynamics of the SMM has the characteristics of multivariable nonlinearity, uncertainties and strong coupling. Uncertainties like the modeling errors and external disturbances affect the tracking performance, and coupling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…of the ORFBLS identifier. By following [28], [32]- [34], it is necessary to find the error objective function 𝐸(𝑘) which is established from the difference among the actual system response 𝒚 and the estimated system response 𝒚 ̂ obtained from (14) in the form:…”
Section:  =  P W W W β a Amentioning
confidence: 99%
“…of the ORFBLS identifier. By following [28], [32]- [34], it is necessary to find the error objective function 𝐸(𝑘) which is established from the difference among the actual system response 𝒚 and the estimated system response 𝒚 ̂ obtained from (14) in the form:…”
Section:  =  P W W W β a Amentioning
confidence: 99%
“…Of course, it can also be concluded that λ * is the optimal solution, and we do not make additional assumptions about matrices A, B and vector B in constraints nor do we require matrices A and B to have perfect permutation. e following will give the convergence result of solving formula (13) with the classical ADMM algorithm:…”
Section: Convergence Of the Classical Admm Algorithmmentioning
confidence: 99%
“…e above formula (21) is called the optimal condition of the classical ADMM algorithm. If x * , y * , λ * is the optimum of formula (13), then formula (21) is satisfied; on the contrary, if there is x * , y * , λ * satisfying (21), it is the best point of (13). In equation ( 21), the first line is called the initial problem feasibility condition; that is, the best point must satisfy the equality constraint of equation (12); the second and third lines are called dual-use conditions, where Operator z represents the subdifferential or subgradient operators that is described in detail in the previous section.…”
Section: Optimal Conditions and Stopping Criteria Of Thementioning
confidence: 99%
See 2 more Smart Citations